PSEUDOHYPOALDOSTERONISM: A CASE REPORT - War, Adilah; Lim, SH (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Pseudohypoaldosteronism is a heterogeneous group of disorders manifested by end-organ resistance to mineralocorticoids. We describe a case of recurrent salt wasting, hyperkalaemia and metabolic acidosis from this condition. RESULTS A 2.5-year-old girl was first presented to us at day 8 of life with poor feeding, lethargy and in circulatory collapse requiring cardiopulmonary resuscitation. She was not dysmorphic, had unremarkable systemic findings with normal female genitalia. Laboratory parameters showed persistent hyponatraemia, hyperkalaemia and hyperchloraemic metabolic acidosis. She was initially treated with steroid therapy, but had shown no clinical improvement. The only significant hormonal work-ups were significantly elevated Renin and Aldosterone levels. Genetic confirmation test unfortunately was not available. Other secondary causes of adrenal resistance were also excluded. She subsequently had a few more episodes of salt-losing crisis, with improvement in terms of severity and the frequency of the event. These episodes were successfully treated with high dose sodium supplements and potassium-binding resin. She is now growing along a low growth percentile curve with reasonable agecorresponding developmental milestones. CONCLUSION Salt wasting crisis carries significant mortality and morbidity in children. Despite being rare, condition such as mineralocorticoid disorder must be considered when response to treatment does not follow common pattern.